On the predictive power of monetary exchange rate model: the case of the Malaysian Ringgit/US Dollar rate. - Baharumshah, Ahmad Zubaidi; Mohd, Siti Hamizah; Sung, Ahn (Taylor & Francis, 2009)
The predictive power of the monetary model for the Malaysian ringgit/US dollar (RM/USD) rate is analysed using quarterly data ending in 2006:Q3. We find compelling evidence of a long-run relationship between exchange rates and the economic fundamental determinant. Macroeconomic factors systematically affect the long-run movement of the RM/USD rate. Additionally, the RM/USD rate was overvalued by about 10% severalquarters before the 1997 crisis; after the crisis, rates fluctuated close to the equilibrium value. The out-of-sample forecasts demonstrate that the monetary model outperforms the naı¨ve random walk model. The monetary and Purchasing Power Parity (PPP) models do well at the four to eight quarters horizon.